2018
DOI: 10.1371/journal.pone.0190846
|View full text |Cite
|
Sign up to set email alerts
|

Impaired resolution of DSS-induced colitis in mice lacking the glucocorticoid receptor in myeloid cells

Abstract: Inflammatory bowel disease (IBD) is a highly prevalent intestinal disorder for which no cure exists. Currently, the standard first-line treatment of IBD consists of systemic glucocorticoid (GC) application, even though therapy can be complicated by unresponsiveness or adverse effects. In view of the importance of macrophages and neutrophils for the pathogenesis of IBD we set out to define the relevance of these cell types as targets of GC using the mouse model of DSS-induced colitis. We found that the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 43 publications
(60 reference statements)
3
42
0
3
Order By: Relevance
“…9). Our data correspond well with those of Leung et al ., who reported that M2 macrophages inhibited colitis in a dinitrobenzene sulfonic murine colitis model 82,83 . ARG1 was originally hypothesized to promote Th2-driven inflammation 8486 .…”
Section: Discussionmentioning
confidence: 99%
“…9). Our data correspond well with those of Leung et al ., who reported that M2 macrophages inhibited colitis in a dinitrobenzene sulfonic murine colitis model 82,83 . ARG1 was originally hypothesized to promote Th2-driven inflammation 8486 .…”
Section: Discussionmentioning
confidence: 99%
“… 66 In a model of colitis induced by dextran sulfate sodium (DSS) using the GR LysM- Cre mouse model, it was shown that GR signaling in myeloid cells is required to resolve inflammation. 67 GCs also upregulate the expression of CD163, a scavenger receptor that is a marker of alternatively activated macrophages, in human monocytes and macrophages 68 , 69 and increase the ability of human macrophages to engulf apoptotic cells via phagocytosis, thereby contributing to the resolution of inflammation. 70 , 71 …”
Section: Myeloid Cells Are the Main Targets Of Gc Smentioning
confidence: 99%
“…Thus, the intestinal milieu was probably reflecting a resolution state, rather than a pro-inflammatory response with high cytokine concentrations, even if the inflammatory cells were still physically present in the microenvironment. Supporting our premise are studies of DSS-induced colonic tissue that show reduced cytokine production at the mRNA or protein levels in the resolution phase compared to the acute phase of inflammation (2426).…”
Section: Discussionmentioning
confidence: 59%